2022
DOI: 10.3389/fcimb.2022.857035
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Gut Dysbiosis and Sepsis-Induced Myocardial Dysfunction in Patients With Sepsis or Septic Shock

Abstract: ObjectiveSepsis-induced myocardial dysfunction (SIMD) seriously affects the evolution and prognosis of the sepsis patient. The gut microbiota has been confirmed to play an important role in sepsis or cardiovascular diseases, but the changes and roles of the gut microbiota in SIMD have not been reported yet. This study aims to assess the compositions of the gut microbiota in sepsis or septic patients with or without myocardial injury and to find the relationship between the gut microbiota and SIMD.MethodsThe pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
1
9
1
Order By: Relevance
“…Compared to non-SIC patients, SIC patients showed higher SOFA and APACHE II scores, as well as higher levels of CK-MB, BNP, TnI, lactate, and PCT. This conclusion was consistent with those presented in earlier studies [48][49][50][51][52]. RAAS was stimulated and the Ang II levels are elevated during the initial sepsis stages [53].…”
Section: Discussionsupporting
confidence: 93%
“…Compared to non-SIC patients, SIC patients showed higher SOFA and APACHE II scores, as well as higher levels of CK-MB, BNP, TnI, lactate, and PCT. This conclusion was consistent with those presented in earlier studies [48][49][50][51][52]. RAAS was stimulated and the Ang II levels are elevated during the initial sepsis stages [53].…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of Actinobacteria was signi cantly reduced in patients with septic cardiomyopathy compared to those with non-septic cardiomyopathy. In contrast, a previous study by Chen Y et al [37] showed that patients with septic cardiomyopathy were characterized by an increase in Proteobacteria and a decrease in Bacteroidota at the portal level, which is inconsistent with our ndings. Combining multiple relevant factors that affect the gut microbiota [38] , including geography, diet, nutritional support, and antibiotic use, I must interpret our ndings cautiously here.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of preclinical experiments and clinical studies have reported the association between gut microbiota and sepsis. 10,[33][34][35][36][37][38][39] Several preclinical models have shown that disruption of the microbiota with antibiotics, paradoxically, increases the risk of bloodstream infections and critical illness. 11,12 This potential association has additionally been confirmed in the US Health and Retirement Study, in which a strong and consistent longitudinal dose-response relationship between suggested dysbiosis and progression to sepsis.…”
Section: Discussionmentioning
confidence: 99%